2020
DOI: 10.1039/d0cc00427h
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent structural locking of thermoresponsive polyion complex micelles, nanowires, and vesicles via polymerization-induced electrostatic self-assembly using an arginine-like monomer

Abstract: The noncovalent locking of nanostructured thermoresponsive polyion complexes can be achieved via polymerization-induced electrostatic self-assembly (PIESA) using an arginine-like cationic monomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 41 publications
0
47
0
Order By: Relevance
“…The thermal behavior of nanoparticles prepared with an inherently different aqueous PISA protocol was reported recently by Cai and co-workers in 2020. 45 In contrast to the previously discussed formulations, this aqueous PISA formulation is based on the chain extension of a macromolecular chain transfer agent (macro-CTA), poly[N-(2-hydroxypropyl)methacrylamide], with a charged core-forming monomer in the presence of an oppositely charged homopolymer. The resulting nanoparticles are polyion complexes.…”
Section: Raft-pisamentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal behavior of nanoparticles prepared with an inherently different aqueous PISA protocol was reported recently by Cai and co-workers in 2020. 45 In contrast to the previously discussed formulations, this aqueous PISA formulation is based on the chain extension of a macromolecular chain transfer agent (macro-CTA), poly[N-(2-hydroxypropyl)methacrylamide], with a charged core-forming monomer in the presence of an oppositely charged homopolymer. The resulting nanoparticles are polyion complexes.…”
Section: Raft-pisamentioning
confidence: 99%
“…Repeat units of opposite charge can also be introduced as (or within) a third block, leading to spheres, worms, vesicles, and lamella. 45,163,164 Moreover, it is worth mentioning that Cai and co-workers 165 recently established a well-considered seeded RAFT-PIESA protocol that allowed the preparation of multicompartmentalized micelles, nanosheets, and nanocages. This work is based on the synthesis of a positively charged diblock copolymer in the presence of an oppositely charged nonreactive diblock copolymer sphere.…”
Section: Conclusion/perspectivementioning
confidence: 99%
“…These observations indicated that the aromatic interactions among benzene core were weakened and the indole side chain participated in stronger π-π stacking. [47] Taken together, it could be concluded that higher H 2 O contents could lead to stronger hydrogen bonding and induced π-π interactions among LPWM molecules. Note that the decrease in the integral of the signals upon increasing the D 2 O content was likely caused by its migration from the liquid phase into an aggregative phase, the existence of buried monomers inside the nanostructures was considered not accessible to the solvent.…”
Section: Transition Mechanism From Nanospheres To Nanofibersmentioning
confidence: 95%
“…More recently, Zhao et al prepared thermoresponsive polyion complex (PIC) nanostructures through polymerization-induced electrostatic self-assembly (PIESA) of a cationic arginine-like core-forming monomer, namely, N -(2-guanidinoethyl)methacrylamide (GEMA), and simultaneous non-covalent structural locking with anionic poly(2-acrylamido-2-methylpropanesulfonic acid) (PAMPS) by H-bonding [ 105 ]. Visible light-initiated RAFT polymerization of GEMA was performed in an acidic aqueous solution of PAMPS at 25 °C using a hydrophilic poly( N -2-hydroxypropylmethacrylamide) (PHPMAm) macro-CTA as the corona-forming block.…”
Section: Amino Acid-based Nanostructures Via Pisamentioning
confidence: 99%
“…More recently, Zhao et al prepared thermoresponsive polyion complex (PIC nanostructures through polymerization-induced electrostatic self-assembly (PIESA) of cationic arginine-like core-forming monomer, namely, N-(2-guanidinoethyl)methacryla mide (GEMA), and simultaneous non-covalent structural locking with anionic poly(2 More recently, Zhao et al prepared thermoresponsive polyion complex (PIC) nanostructures through polymerization-induced electrostatic self-assembly (PIESA) of a cationic arginine-like core-forming monomer, namely, N-(2-guanidinoethyl)methacrylamide (GEMA), and simultaneous non-covalent structural locking with anionic poly(2-acrylamido-2-methylpropanesulfonic acid) (PAMPS) by H-bonding [105]. Visible light-initiated RAFT polymerization of GEMA was performed in an acidic aqueous solution of PAMPS at 25 • C using a hydrophilic poly(N-2-hydroxypropylmethacrylamide) (PHPMAm) macro-CTA as the corona-forming block.…”
Section: Amino Acid-based Nanostructures Via Pisamentioning
confidence: 99%